Distinct YFV Lineages Co-circulated in the Central-Western and Southeastern Brazilian Regions From 2015 to 2018 - Delatorre, Edson; Abreu, Filipe Vieira Santos de; Ribeiro, Ieda Pereira; Gómez, Mariela Martínez; dos Santos, Alexandre Araújo Cunha; Ferreira-de-Brito, Anielly; Neves, Maycon Sebastião Alberto Santos; Bonelly, Iule; de Miranda, Rafaella Moraes; Furtado, Nathália Dias; Raphael, Lidiane Menezes Souza; da Silva, Lucileis de Fátima Fernandes; et al. (Frontiers in Microbiology, 2019)
The current outbreak of yellow fever virus (YFV) that is afflicting Brazil since the end of 2016 probably originated from a re-introduction of YFV from endemic areas into the non-endemic Southeastern Brazil. However, the lack of genomic sequences from endemic regions hinders the tracking of YFV’s dissemination routes. We assessed the origin and spread of the ongoing YFV Brazilian outbreak analyzing a new set of YFV strains infecting humans, non-human primates (NHP) and mosquitoes sampled across five Brazilian states from endemic and non-endemic regions between 2015 and 2018. We found two YFV sub-clade 1E lineages circulating in NHP from Goiás state (GO), resulting from independent viral introductions into the Araguaia tributary river basin: while the strain from 2017 clustered intermingled with Venezuelan YFV strains from 2000, the YFV strain sampled in 2015 clustered with sequences of the current YFV outbreak in the Brazilian Southeastern region (named YFV2015-2018 lineage), displaying the same molecular signature associated to the current YFV outbreak. After its introduction in GO at around mid-2014, the YFV2015-2018 lineage followed two paths of dissemination outside GO, originating two major YFV sub-lineages: 1) the YFVMG/ES/RJ sub-lineage spread sequentially from the eastern area of Minas Gerais state to Espírito Santo and then to Rio de Janeiro states, following the Southeast Atlantic basin; 2) the YFVMG/SP sub-lineage spread from the southwestern area of Minas Gerais to the metropolitan region of São Paulo state, following the Paraná basin. These results indicate the ongoing YFV outbreak in Southeastern Brazil originated from a dissemination event from GO almost two years before its recognition at the end of 2016. From GO this lineage was introduced in Minas Gerais state at least two times, originating two sub-lineages that followed different routes towards densely populated areas. The spread of YFV outside endemic regions for at least four years stresses the imperative importance of the continuous monitoring of YFV to aid decision-making for effective control policies aiming the increase of vaccination coverage to avoid the YFV transmission in densely populated urban centers.